Giving Automated Feedback About Student Code Identifiers: a Method Based on the Description of Programming Problem - Nascimento, Marcos; Araújo, Eliane; Serey, Dalton; Figueiredo, Jorge (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2019)
Providing timely feedback on identifier naming to novice programmers can help them to improve their program readability. However, due to the growth in the number of students learning to program nowadays, giving manual feedback on identifier quality becomes prohibitive. In this paper, we propose a method to automatically give this feedback which is correct 75.0% of the time in contrast to the instructors' assessment. We found that 51.7% of the students who received automated feedback showed their program identifier quality improvement by picking better names. It means that we can help students to improve identifier naming and consequently, their program readability from early coding experiences.